Guided imagery relaxation therapy on preoperative anxiety: a randomized clinical trial - Márcia Marques dos Santos Felix; Maria Beatriz Guimarães Ferreira; Lucas Felix de Oliveira; Elizabeth Barichello; Patricia da Silva Pires; Maria Helena Barbosa (Revista Latino-Americana de Enfermagem, 2018)
Objective to evaluate the effect of relaxation therapy with guided imagery on state anxiety and cortisol in the immediate preoperative period in patients submitted to bariatric surgery by videolaparoscopy. Method a randomized, triple-blind clinical trial in a large teaching hospital in the interior of Minas Gerais. Twenty-four patients who would undergo video-laparoscopic bariatric surgery were randomly allocated in two groups, namely 12 in the control group and 12 in the experimental group. State anxiety was assessed by the State-Trait Anxiety Inventory, and blood cortisol levels were measured before and after the intervention or standard care. Descriptive analyzes were used for the quantitative variables and Student’s t-test for independent samples, in the analysis of the differences between the state anxiety scores and cortisol levels. Results the experimental group presented a statistically significant reduction of the state anxiety scores (p = 0.005) as well as of cortisol levels (p <0.001) after the intervention. Conclusion guided imagery relaxation therapy is an effective nursing intervention for the reduction of state anxiety and blood cortisol levels in the preoperative period in patients undergoing video-laparoscopic bariatric surgery. Brazilian Registry of Clinical Trials: RBR-5qywrf.